CONTRIBUTION OF THE CROP SUB-SECTORS’ PERFORMANCE TO THE ECONOMIC DEVELOPMENT OF NIGERIA: THE ARDL MODEL APPROACH - Sunday Brownson AKPAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study examined the contributions of sub-units of the crop subsector to the economic development of Nigeria (approximated by the per capita GDP (PCI)) from 1962 to 2020. The Autoregressive Distributed Lag Model (ARDL) was used to establish the existence of the cointegration among the specified series. The findings revealed that, the sub-components of the crop sub-sector co-integrate with the per capita GDP in the long run. The empirical results further revealed that in the short run, sugar-based crops gross production, vegetable, and fruit gross production have a significant relationship with the PCI in Nigeria; whereas the cereal gross production, oil-based crop gross production, sugar crop gross production, and vegetable and fruit gross production were long run significant determinants. The findings call for appropriate short and long-term economic policy packages that should stimulate investment opportunities in the crop sub-sector to increase the sub-sector’s productivity for greater economic development stimulation.